Architecture Storytelling of the Stanford Torus: A Symbolic-Narrative Analysis in Science Fiction Media - Naldo Yanuar Heryanto (Jurnal Riset Arsitektur, 2026)
This study examines the representation of toroidal architecture, particularly the Stanford Torus, in selected science fiction works such as Elysium (2013), Interstellar (2014), 2001: A Space Odyssey (1968), Mass Effect (2007), Mobile Suit Gundam (1979), and Star Wars: The Book of Boba Fett (2021). While previous studies on science fiction architecture that tends to emphasize technological speculation or visual spectacle, limited attention has been given to architecture as an active narrative and ideological agent across different media. Using a qualitative-descriptive approach that combines Bordwell–Thompson’s narrative theory and Charles Jencks’ architectural symbolism, this research explores how spatial architecture functions as a medium of storytelling and as a constructor of social, political, and existential meaning in visions of humanity’s future. The Torus form operates not merely as a futuristic setting but as a symbolic narrative structure that reflects tensions between technological progress, social hierarchy, and spiritual longing in modernity. Across media, toroidal architecture functions as a visual metaphor for a closed civilizational system, simultaneously embodying utopian sustainability and dystopian social exclusivity. This study contributes theoretically by positioning toroidal architecture as a key analytical entry point in architectural narratology and visual culture studies, demonstrating how imagined space articulates contemporary ideological anxieties.